Curdione combined with borneol treats bacterial mixed HPV infection by regulating the crosstalk among immune cells - Liu, Jingwei; Shu, Tong; Mu, Yiheng; Zheng, Wanlin; Lu, Xiaohuan; Tao, Hong (Frontiers in Immunology, 2025)
BackgroundHuman papillomavirus (HPV) infection is a worldwide reproductive system disease. Baofukang suppository, a traditional herbal preparation that includes curdione and borneol, has been reported to treat bacterial vaginosis (BV) and HPV infection in China. However, the therapeutic mechanism is still unknown. This study aims to explore the molecular mechanisms of curdione and borneol in treating HPV infection.MethodsWe conducted a retrospective cohort analysis of medical records from a single-center study involving 205 HPV patients, focusing on the correlation between HPV clearance and co-infection with other pathogens, confirming the efficacy of Baofukang suppository. Bioinformatics and network pharmacology approaches were employed to identify therapeutic targets of Baofukang suppository for BV/HPV co-infections. qRT-PCR, Western blot, immunofluorescence staining, and flow cytometry were utilized to validate the therapeutic targets of curdione and borneol, along with the associated immune molecular changes. Finally, the molecular mechanisms and therapeutic efficacy of curdione and borneol were confirmed in vivo using an LPS/TC-1 cervical orthotopic injection model.ResultsCurdione and borneol selectively inhibit the secretion of interleukin-6 (IL-6) and interleukin-1β (IL-1β) by macrophages. The reduction in IL-6 and IL-1β levels effectively inhibits the expression of CD274 (Programmed death ligand 1, PD-L1) in infected epithelial cells by inhibiting STAT3 phosphorylation, thereby suppressing their immune evasion capabilities. Furthermore, curdione and borneol enhance the expression of tumor necrosis factor α (TNF-α) and caspase 1 (CASP1) in macrophages, as well as the expression of interleukin 12 (IL-12) and interleukin 23 (IL-23) in dendritic cells (DCs). The expression of these inflammatory factors effectively promotes the migration and differentiation of T cells to the site of infection, completing the clearance of infected epithelial cells.ConclusionThe main components of Baofukang suppository, curdione and borneol, inhibit the progression of HPV infection and the occurrence of cervical cancer by modulating the communication between innate and adaptive immunity, promoting the recruitment and recognition of CD8+ T cells to eliminate HPV-infected epithelial cells.